Implementasi Ekstrakurikuler Pramuka Dalam Meningkatkan Prestasi Pramuka di MI Kwadungan Lor - Septiani, Indri Septiani; Koesmadi, Dita Primashanti; Afifah, Uci Ulfa Nur’ (Jurnal Ilmiah Global Education, 2025)
This study aims to describe the implementation of Scouting extracurricular activities in improving student achievement at MI Kwadungan Lor. The background of this study is the importance of extracurricular activities as a vehicle for character development, social skills, and non-academic achievements of students. Scouting extracurricular activities were chosen because they have strong educational values ​​in forming discipline, responsibility, cooperation, and leadership. This study uses a qualitative approach with a descriptive study type. The subjects of the study consisted of Scout instructors, madrasah principals, and active students in extracurricular activities. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of Scouting extracurricular activities at MI Kwadungan Lor was carried out through three main stages, namely planning, implementation, and evaluation. Activity planning is carried out through routine meetings and the preparation of annual work programs that consider the capabilities of resources and the needs of students. Implementation of activities includes weekly routine training and intensive training before the competition, with a fun and participatory approach. Evaluation of activities is carried out periodically to assess the effectiveness of the program and as a basis for improvement. The main supporting factors for the success of this activity include the commitment of the instructor, the support of the head of the madrasah, the enthusiasm of the students, and the cooperation of the parents